2022
DOI: 10.1029/2022wr032720
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Density Gradients on the Secondary Flow Structure of a River Confluence

Abstract: A greater understanding of these structures is therefore of obvious interest. Four structures are often discussed: helical cells (secondary flow at the scale of the tributaries' widths), vertically orientated Kelvin-Helmholtz (KH) vortices (shear-induced instabilities along the mixing interface), episodic pulses (origins still not fully understood, see Sabrina et al. (2021)) and streamwise orientated vortices (SOVs). SOVs were first discovered in numerical models as a pair of back-to-back, counter-rotating SOV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 44 publications
6
14
0
Order By: Relevance
“…The Froude number of the left channel (F r = U/ √ gD, where U l is taken as U) in the slow experiments was 0.048, similar in magnitude to the F r of 0.04 of the Massawippi during the density SOV observations of Duguay et al (2022b). The Froude number of the right channel (F r = 0.086) is also of similar magnitude to that of the Coaticook (0.12) in Duguay et al (2022b). The values of ρ straddle that of 0.50 kg m −3 estimated between the Coaticook and Massawippi rivers during the coherent density SOV observations of July 9th, 2020, discussed by Duguay et al (2022a).…”
Section: Tested Flow Conditionssupporting
confidence: 55%
See 1 more Smart Citation
“…The Froude number of the left channel (F r = U/ √ gD, where U l is taken as U) in the slow experiments was 0.048, similar in magnitude to the F r of 0.04 of the Massawippi during the density SOV observations of Duguay et al (2022b). The Froude number of the right channel (F r = 0.086) is also of similar magnitude to that of the Coaticook (0.12) in Duguay et al (2022b). The values of ρ straddle that of 0.50 kg m −3 estimated between the Coaticook and Massawippi rivers during the coherent density SOV observations of July 9th, 2020, discussed by Duguay et al (2022a).…”
Section: Tested Flow Conditionssupporting
confidence: 55%
“…a discharge-weighted average of the tributaries' bulk velocities, the bulk velocity of the tributary or the bulk velocity of the main channel). Also, Duguay et al (2022b) showed that F D is incapable of accounting for the effects that the sign of the density gradient has on secondary flow structure (i.e. a fast denser channel encountering a slow light channel produces different structures than a fast-light channel encountering a slow-dense channel).…”
Section: The Densimetric Froude Numbermentioning
confidence: 99%
“…Table 1 also lists the water chemistry characteristics, and the relative density difference Δ ρ observed during the field surveys. A notation is adopted to convey both the magnitude and direction of ∆ ρ (Duguay et al., 2022b). In Survey 1, the Yangtze River was estimated to be 0.9 kg/m 3 denser than the Poyang Lake and because the Yangtze River is the left tributary, density decreased across the mixing interface from left to right.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, the density effects might have been weakened by the larger relative bed roughness associated with the lower water depth in Survey 3 (Best & Roy, 1991;Constantinescu et al, 2016). On the other hand, the density effect of Survey 3 may not be as large as the density Froude number indicated (Duguay et al, 2022b;Pouchoulin et al, 2020).…”
Section: Density Differencementioning
confidence: 98%
“…The extent to which even weak vertical stratification can modify the generalized flow patterns of confluences has been investigated computationally (Ramon et al, 2014, 2016; Horna‐Munoz et al, 2020; van Rooijen et al, 2020) and has been confirmed in the field at confluences where density effects are relatively strong (Herrero et al, 2018; Ramon et al, 2013), but extensive field investigations are lacking. Recent work suggests that even small density effects can produce local effects on flow structure in the vicinity of the mixing interface (Duguay et al, 2022a, 2022b).…”
Section: Introductionmentioning
confidence: 99%